PENGARUH FREE CASH FLOW TERHADAP UTANG - Heru Nurwahyudi; Aida Ainul Mardiyah (Media Riset Akuntansi, Auditing & Informasi, 2004)
The objective of this research is to analysis and giving the empirical evidence about the free cas flow and the effect of it for debt policy of public companies in Indonesia. This research was using 66 samples of manufacturing companies in the year 2000 and 90 sample of manufacturing in the year 2001. This sample was elected based on purposive sampling, the hypothesis test is the simple tinier regres-sion.The result of this research showed that hypothesis were suppo4ted, there are influence of free cash flow to the debt policy. In the agency relationship there is differences interest between the principal and the manager also created agency problems that finally also create agency cost. In the shareholders (agents) point of view, this can be minimize by the third party (debtho!der) whose come by the debt policy. Increasing financing with debt will reduce the conflict between the sharehold-ers and the management.Keywords: Free cash flow, debt